The Graeco-Buddhist style of Gandhara: a “Storia ideologica”, or: how a discourse makes a global history of art - Falser, Michael (Journal of art historiography, 2015)
This paper is embedded in the new methodological - transcultural - approach of Global Art History: it questions the taxonomies and values built into the discipline since its inception, with their claim to universal validity, and tries to constitute new units of investigation by contextualizing the multiple processes of the appropriation and reconfiguration of artworks through the participating agents in changing institutional regimes. As a case-study, this paper investigates what art historians and archaeologists between 1850 and 2015 had negotiated under the umbrella-term Graeco-Buddhist Style of Gandhara as it historically emerged in an area of today’s North Pakistan between the first and fifth centuries CE. Bypassing the Area Studies approach to describe this Eurasian hybrid of architectural and sculptural style along its formal characteristics, this paper investigates how it was ideologically exploited for different (post)colonial purposes by operating with the classic art historical terminologies of influence and transfer, purity and decadence.